PENGARUH PELAYANAN PUBLIK TERHADAP KEPUASAN PELANGGAN PADA DINAS PERHUBUNGAN KOTA DEPOK - Bilgah Bilgah (Cakrawala - Jurnal Humaniora, 2018)
ABSTRACTThe quality of public services is the extent to which a public facility (public) in providing services to the public. The government is required to provide quality public services. Society can be satisfied from service apparatus (government) only oriented to total customer satisfaction. In providing quality services to the community in this case the customers who come, Cilodong District Office of Depok City has a goal to create optimal service so that people feel comfortable and satisfied with the services provided. The executor of the public service department at the Cilodong District Office, Depok City is always swift in providing services to customers, proved the quality of services provided to customers positively affect the satisfaction of the community. Can be seen from the regression line that Y = 10,658 + 0,745X this indicates that existence of positive and strong influence between public service and customer satisfaction. And based on the calculation of the correlation of 0.745 or 74.5% which shows the strong and positive relationship between the quality of public service to the satisfaction of the community or the customer.  Keywords: Public Service, Customer Satisfaction